Directions of spiritual and educational activity - Rakhimov Asomiddin Anorboevich (Proceedings of The ICECRS, 2020)
This article highlights the role of spiritual and educational activity in the context of education reform requirements and its role in human development. It also describes the main tasks and directions of spiritual and educational activities